The Roles of Teachers in Improving Students' Basic English Reading Skills of SMP Swasta Idanoi in 2024/2025 - Suriani Ndraha; Riswan Zega; Yaredi Waruwu; Elwin Piarawan Zebua (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study aims to analyse the role of teachers in improving basic English reading skills and how teachers improve basic English reading skills at School SMP Swasta Idanoi. There are two people who participated in this research, namely the English teacher. The methods used in this research are observation, interview. The researcher collected data through observation and interview. To support this research data, researchers took documentation. The research data processing was done with three stages, namely data reduction, display and conclusion. Based on the results of the study, the researcher found two teacher roles in improving basic English reading skills that have been carried out from eight related teacher roles, namely, providing reinforcement and motivation to students, and following the curriculum. And then the way teachers in improving basic English reading skills teachers provide reinforcement and motivation to students, such as if there are mistakes and shortcomings of students in learning teachers give understanding to these students in terms of telling the correct learning, and follow the curriculum or Formal methods at school which are the basis for teachers to carry out learning such as making lesson plans. The researcher suggests that teachers introduce letters and sounds to students, build basic vocabulary in students, read short words to students, provide basic reading practice to students, use technological media in teaching, and provide additional lessons to students.